Analytical inverse kinematic computation for 7-DOF redundant sliding manipulators. (January 2021) - Tong, Yuchuang; Liu, Jinguo; Liu, Yuwang; Yuan, Yuan
Highlights: This study proposes an analytical inverse kinematic parameterized method. The method is extended to all-types of redundant sliding manipulators. The structural characteristics of redundant sliding manipulators are analyzed. This method adopts the Newton-Raphson algorithm for secondary adjustment. Simulation and physical experiments verify the effectiveness and universality. Abstract: The shape and movement irregularities of rail-type redundant sliding manipulators lead to structural uncertainty, which results in inverse kinematics computations that are considerably more complicated than those of the traditional redundant manipulator currently studied. In this paper, an analytical inverse kinematic parameterized method is proposed for the redundant sliding manipulators, which solves the inverse kinematics analytically and adopts the Newton–Raphson algorithm for secondary adjustment. This paper is the first time to propose a general analytical inverse kinematics solution for all types of rail-type redundant sliding manipulators. Furthermore, the special structural characteristics of the rail-type redundant sliding manipulator are analyzed in this paper. The proposed method takes the redundant circular-sliding manipulator as the research object, and extends to all types of rail-type redundant sliding manipulators. It has the advantages of simplicity, practicability, obvious geometric meaning and universality, which can solve the real-time motion planning and control issues of all types of redundant sliding manipulators. Simulation illustrations and physical experiments are performed to verify the effectiveness and universality of the method.